Aeromobilities in the Time of the COVID-19 Pandemic. Issue 1 (1st March 2020) - Lin, Weiqiang
Abstract: This Perspective piece marks the ten-year anniversary of Transfers ' life as a journal and its contributions to aeromobilities research. Reflecting on my own past decade learning and writing about aeromobilities, the article takes stock of some significant threads in the field, before charting out three key future directions for aeromobilities research prompted by the COVID-19 pandemic and health crisis. Without prejudice to existing scholarly threads, the article discusses the burgeoning salience of new (aero)mobility injustices, automation, and aerial (in)civilities, amid an aviation industry struggling to reboot itself. The next ten years present enduring possibilities for aeromobilities inquiries, and the article hopes to inspire future thinking on the subject as societies connect again through aviation.